Promoting the health of migrant seasonal agricultural workers in rural Minnesota using a whole-person health approach: a pilot project - Jaffer, Shahidali; Hane, Jessica; Eckerstorfer, Margaret; Austin, Robin; Kirsch, Jonathan D. (Frontiers in Public Health, 2025)
IntroductionPromoting the health of the migrant and seasonal agricultural worker (MSAW) community is a unique challenge due to the particular social and economic barriers this community faces. Whole-person health assessments can aid in better understanding the specific needs of a community by accounting for social determinants of health (SDOH) and recognizing and leveraging a community’s strengths to assist in improving community health. To better optimize services provided at outreach health fairs for the MSAW community, the University of Minnesota performed comprehensive whole-health assessments using the mobile health (mHealth) application MyStrengths+MyHealth (MSMH). Results from these assessments were used to augment provided resources at future health events and create new community-specific interventions.MethodsIn August 2022, participants receiving healthcare services from the Mobile Health Initiative (MHI) were asked to complete the MSMH survey. This whole-person health assessment comprises 42 health concepts that utilize participants’ self-reported strengths, challenges, and needs. Participants were provided a financial incentive to complete the assessment.ResultsThirty-one participants completed the MSMH survey. The majority were between the ages of 45–64 (35.5%) and self-identified as female (80.6%), white (64.5%), Hispanic/Latinx (93.5%), married (48.4%), and high school educated (41.9%). Overall, participants had many more strengths than challenges and needs; however, challenges were noted in the Vision (35.5%) and Income (29.0%) domains, leading to targeted interventions to improve these areas at future health outreach events.ConclusionUtilizing a whole-person health assessment framework such as MSMH can result in a more nuanced understanding of a community, including its unique strengths, needs, and challenges. This information can be invaluable for health outreach groups seeking to promote community health by identifying upstream factors contributing to health outcomes. For the MSAW community in Minnesota, MSMH survey data were used to promote community health by increasing services, connecting individuals with community resources, and establishing vision and oral health programs.